The 6% club unlock the secret to achieving any goal and thriving in business and life - Rozen, Michelle (Ascent Audio, 2024)
Learn the steps to build better habits and join the ranks of changemakers and goal achievers everywhere. In The 6% Club, Michelle Rozen, PhD, teaches audiences how to create and actually stick to new positive habits, unlocking the secret formula to the life, success, and happiness they've always dreamed of. The book was born from a recent study where Dr. Rozen surveyed 1,000 people who pledged to make a change in their lives, and, shockingly, only 6% had stuck to the change just a month later. Dr. Rozen's powerful and actionable methods have been tested on countless event attendees from all types of backgrounds for over a decade. Based on science and written by one of the most sought-after motivational speakers on leadership and change, The 6% Club earns a well-deserved spot on the bookshelves of all individuals looking to make lasting changes in their personal and professional lives.
Online resource; title from title details screen (O'Reilly, viewed August 13, 2024)
Keywords: Goal (Psychology); Achievement motivation; Success; Success in business; Motivation d'accomplissement; Succès; Succès dans les affaires; Audiobooks; Livres audio